Hamilton Harty’s Legacy with the Hallé Orchestra (1920-1930): a Reassessment - Plummer, Declan (Journal of the Society for Musicology in Ireland, 2010)
Sir Hamilton Harty is primarily remembered as the principal conductor of the Hallé Orchestra from 1920 to 1933. His conducting career, in comparison to those of other British conductors of the twentieth century, has been neglected. The main research findings for this article conclude that, despite several reassessments of his career, Harty’s legacy remains largely neglected by commentators because of a reliance on inaccurate contemporary criticisms of his supposedly conservative tastes. Apart from the fact that Harty introduced many new compositions and kept a higher percentage of living composers in his programmes than any of his predecessors or successors, he also revived and maintained the highest performance standards for any British orchestra during his tenure, whilst coping with the financial pressures of post-war Britain. In this regard, he was the most successful conductor in Britain during the 1920s and the most successful Hallé conductor of the twentieth century.